Prevalensi refluks laringofaring pada bayi laringomalasia primer - Nasution, Dina Putri; Tamin, Susyana; Hutauruk, Syahrial; Bardosono, Saptawati (Oto Rhino Laryngologica Indonesiana, 2012)
Background: Primary laryngomalacia is a congenital weakness of the supraglottis structures which collapsed during inspiration causing upper airway obstruction. This condition can cause changes in gradient of intrathoraxic-abdominal pressure resulting reflux of gastric juice into the upper airway causing laryngopharyngeal reflux (LPR). Purpose: To find out the prevalence of LPR as a comorbid disease of primary laryngomalacia in infant using fiberoptic laryngoscopy examination, to know the characteristics  of samples, and the correlation between laryngomalacia with LPR. Methods: This is a cross-sectional  study to assess the prevalence of LPR in infants with primary laryngomalacia at Cipto Mangunkusumo Hospital. LPR was diagnosed based on clinical signs from flexible laryngoscopy video records. Result: The prevalence of LPR was 90% in primary laryngomalacia. There were significant differences from three of five clinical findings with LPR, such as arytenoid edema/erythema (p<0,001), ventricular fold edema (p=0,001), and vocal fold edema (p<0,001). Conclusion: Most of the samples with laryngomalacia in this study also have LPR. The presence of LPR could worsen the clinical manifestation and delay the healing of laryngomalacia. Keywords: primary laryngomalacia, fiberoptic laryngoscopy, laryngopharyngeal reflux    Abstrak :  Latar belakang: Laringomalasia primer merupakan kelainan kongenital laring berupa kelemahan pada struktur supraglotis yang terhisap saat inspirasi dan menyebabkan sumbatan jalan napas atas. Kondisi ini dapat menyebabkan perubahan selisih tekanan intra-abdominal/ intratorakal sehingga terjadi refluks cairan lambung ke saluran napas atas, yang menyebabkan refluks laringofaring (RLF). Tujuan: Mengetahui prevalensi RLF pada bayi laringomalasia primer menggunakan pemeriksaan laringoskopi serat optik lentur, mengetahui karakteristik percontoh, dan hubungan laringomalasia primer dengan RLF.  Metode: Penelitian ini adalah penelitian observasional dengan metode potong lintang untuk mengetahui prevalensi RLF sebagai penyakit penyerta pada bayi laringomalasia di Rumah Sakit Cipto Mangunkusumo. Diagnosis RLF ditegakkan berdasarkan tanda klinis dari rekaman video laringoskopi serat optik lentur. Hasil: Prevalensi RLF diperoleh sebesar 90%. Terdapat tiga dari lima tanda klinis RLF yang berbeda bermakna dengan kejadian RLF, yaitu edema/eritema aritenoid (p<0,001), edema plika ventrikularis (p=0,001), dan edema plika vokalis (p<0,001). Kesimpulan: Hampir seluruh percontoh laringomalasia primer disertai dengan RLF. Penyakit penyerta RLF akan memperberat gejala dan memperpanjang waktu penyembuhan laringomalasia.   Kata kunci: laringomalasia primer, laringoskopi serat optik lentur, refluks laringofaring